Effect of Planting Media on the Growth of Red Betel (Piper crocatum Ruiz) Stem Cuttings - Yuda Ady Baskara; Nugraheni Widyawati (The University of Lampung, 2022)
One of the determining factors for the success of red betel (Piper Crocatum Ruiz) stem cuttings is the growing medium used to grow roots and shoots. This study aims to understand the influence of the type of planting media on the growth of roots, shoots, and height of red betel seedlings and to determine the best planting media that supports the growth of red betel roots and shoots. The study was conducted through an experiment using a Randomized Block Design, consisting of 6 types of planting media and each treatment was repeated four times. The treatments were 1. Sand, 2. Soil, 3. Husk biochar, 4. Soil + Husk biochar, 5. Soil + Sand, 6. Husk biochar + Sand. The research data were analyzed using Analysis of Variance and continued with Duncan Multiple Range Test at 5% level. The results showed that the type of media for growing red betel stem cuttings had an effect on root length, number of shoots, available N. The type of planting media that best supports the growth of roots, shoots and plant height of red betel stem cuttings is husk biochar planting media. Keywords: Planting media, Red betel, Stem cuttings, Root growth, Plant height.